1986
DOI: 10.1128/aem.51.1.157-162.1986
|View full text |Cite
|
Sign up to set email alerts
|

Activity Measurements of Planktonic Microbial and Microfouling Communities in a Eutrophic Estuary

Abstract: 3H]thymidine incorporation, the rate of reduction of iodonitrotetrazolium violet (INT) to INT formazan normalized to DNA, and the ratio of ATP to DNA were adapted to measure the activity of attached and unattached microbial assemblages of Bayboro Harbor, Fla. Activity measurements by [3H]thymidine incorporation were made of cells attached to polystyrene culture dishes, in unfiltered water samples, and in the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The donors also survived better in the experiments (2 and 3) in which they were enumerated. This was consistent with reports of submerged surfaces providing sites of nutrient accumulation [23] and attached microbial assemblages being more active than planktonic cells [24]. In Experiments 2 and 3 the heterotrophic, epilithic bacteria originally inoculated into the liquid phase, also survived better on the discs.…”
Section: Discussionsupporting
confidence: 91%
“…The donors also survived better in the experiments (2 and 3) in which they were enumerated. This was consistent with reports of submerged surfaces providing sites of nutrient accumulation [23] and attached microbial assemblages being more active than planktonic cells [24]. In Experiments 2 and 3 the heterotrophic, epilithic bacteria originally inoculated into the liquid phase, also survived better on the discs.…”
Section: Discussionsupporting
confidence: 91%
“…Although, the lag phase of the curves include the saturation times of CO, in aqueous media before reaching the KOH solution, interference of the transfer of CO, from the culture medium to the absorbent solution was not considered due to buffered culture medium (pH 7.0), and sufficient surface area and volume of both culture medium and KOH solution (Martens 1987 ;Owens et al 1989 ;Ascon-Reyes et al 1995). Greater or smaller activity of adhered cells in comparison to suspended cells depends on the type of cellular activity to be evaluated, and the technique utilized to measure the activity (Brigth and Fletcher 1983 ;Fletcher 1986;Jeffrey and Paul 1986b;Diekmann and Hampel 1989;Galazzo and Bailey 1990). A culture of adhered cells can have a high substrate assimilation rate and a low substrate respiration rate (Fletcher 1986;Galazzo and Bailey 1990), or low growth rate and a high substrate degradation rate (Diekmann and Hampel 1989 ;Ait-Langomazino et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the activity of the adhered cells may be higher or lower than that of the suspended cells. However, as it has been established, the greater or smaller activity of adhered cells on solid surfaces depends principally on physico-chemical properties of the support, physiological state of the cells, medium composition, and culture conditions (Mozes and Rouxhet 1985;Jeffrey and Paul 1986b;McEIdowney and Fletcher 1986).…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55] However, it is unwise to make sweeping generalizations as there are variations in each organism's ability to bind to surfaces. 31,[56][57][58] Furthermore, Habash et al 52 found that under minimal growth conditions, 67% of an adherent Pseudomonas aeruginosa strain were metabolically active, while only 2% were active in the absence of nutrients. Under minimal growth conditions, the level of metabolic activity of the adherent Pseudomonas aeruginosa translated into a generation time of 136 minutes.…”
Section: Growth and Colonizationmentioning
confidence: 99%